STUDY OF FACTORS AFFECTING CONSUMER PURCHASE INTENTIONS FOR OVER-THE-TOP SERVICES - Yadamsuren, Anudari; Ganbold, Munkhbayasgalan (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
In recent years, Over-the-Top (OTT) services have become widely used, increasingly replacing traditional television and cable services. This study aims to identify the factors influencing Mongolian consumers’ intention to use OTT services based on the Technology Acceptance Model (TAM). A total of 372 respondents aged 16 and above residing in Ulaanbaatar participated in the survey. Data were analyzed using SPSS, including reliability testing, factor analysis, and regression analysis. The results indicate that content quality, entertainment, perceived value, and electronic word-of-mouth (e-WOM) have a significant positive influence on consumers’ intention to use OTT services. However, the core TAM variables—perceived ease of use and perceived usefulness—did not show statistically significant effects.